DEFLASI DAN RESESI EKONOMI: PERAN EKONOMI SYARIAH SEBAGAI SOLUSI ALTERNATIF DI INDONESIA - Mutia, Rahmi; Iskandar, Iskandar (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2025)
This study aims to analyze the prolonged deflation phenomenon in Indonesia during May- September 2024 and January - February 2025, as well as the potential accompanying recession. The decline in public demand and contraction in strategic sectors are identified as the main factors driving this condition. In response, the study explores the role of Islamic economics as an alternative solution, emphasizing wealth distribution principles through zakat, infak, and waqf, which are believed to offer a fair and sustainable approach. The methodology involves a literature review and descriptive analysis of secondary data, providing a comprehensive understanding of the economic situation and the potential for Sharia-based interventions. The findings indicate that the application of Islamic economic principles has significant potential to stabilize the economy, alleviate deflationary pressures, and prevent recession by strengthening household consumption, enhancing public welfare, and promoting more equitable resource distribution. These results contribute scientifically by offering the perspective of Islamic economics as an alternative in addressing macroeconomic crises, while highlighting the relevance of Islamic principles in contemporary economic policy. This study is expected to serve as a reference for policymakers and academics in designing more inclusive and equitable recession prevention strategies.